2019
DOI: 10.1088/1361-6463/ab3dc9
|View full text |Cite
|
Sign up to set email alerts
|

Titanium-based ohmic contacts in advanced CMOS technology

Abstract: Since the contact resistance characterized by a specific contact resistivity (ρ c ) in the source/ drain (S/D) regions is becoming a bottleneck for further improving device performance, the criteria for selecting S/D contact materials, e.g. silicides, is therefore more concerned with the ρ c in state-of-the-art fin channel field-effect-transistors rather than the sheet resistance (R sh ) of silicides in conventional planar devices. In these circumstances, Ti-based ohmic contacts prevail over Ni(Pt)Si-based one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 102 publications
1
13
0
Order By: Relevance
“…The stable phase, C54-TiSi2, with a low resistivity (15-20 µΩ.cm), is formed from C49-TiSi2 at higher temperatures between 700 and 850°C 7,[9][10][11] . For advanced imagers technologies as well as 3D FinFETs, TiSi2 contacts are formed through the "salicide last" process with a single-step RTA at high temperature without any selective etch of the unreacted Ti layer 12,13 . This is different from the "salicide first" process which implies two RTA (the first one at low temperature and the second at high temperature) with a selective etch of the unreacted metal between the two RTA steps 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The stable phase, C54-TiSi2, with a low resistivity (15-20 µΩ.cm), is formed from C49-TiSi2 at higher temperatures between 700 and 850°C 7,[9][10][11] . For advanced imagers technologies as well as 3D FinFETs, TiSi2 contacts are formed through the "salicide last" process with a single-step RTA at high temperature without any selective etch of the unreacted Ti layer 12,13 . This is different from the "salicide first" process which implies two RTA (the first one at low temperature and the second at high temperature) with a selective etch of the unreacted metal between the two RTA steps 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pre-amorphous implantation (PAI) is reported to be effective to improve the performance of Ti silicide. Mao et al [ 140 ] and Yu et al [ 141 ] have demonstrated that when a low-energy pre-amorphous Ge implantation is applied on contact area, it will lead to great conductivity improvement, and an extremely low ρ of about 1.5 × 10 −9 Ωcm could be achieved. The mechanism could be explained by the interfacial morphology promotion induced by PAI.…”
Section: Implantation and Advanced Doping Methodsmentioning
confidence: 99%
“…On the basis of the set oxygen flow, the [O/Ga] molar ratio was regulated to be ~1657. Specifically, according to the Antoine's equation [41,42], where P MO is the vapor…”
Section: Methodsmentioning
confidence: 99%
“…, where n mo is the molar flow rate of TMGa, F is the flow rate of carrier = × × ( -) gas, V m = 22414 cm 3 /mol (ideal gas molar volume), P bub is the pressure inside the bubbler. Ohmic contacts [42]. Before the Ni/Au electrodes deposition, the β-Ga 2 O 3 thin film was surface treated by O 2 plasmas for 30 s [43][44][45].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation